Mathematical laboratory and learning of mathematics in 2nd grade secondary students I.E “José Faustino Sánchez Carrión N°0051” Ugel 06-Carapongo-Lima, 2023 - Alarcón Cabrera, Joselyn (2023)
The aim of this research was to demonstrate that the implementation of a mathematics laboratory has a significant impact on the mathematics learning process for 2nd-year secondary students at the educational institution "José Faustino Sánchez Carrión N°0051". The adopted methodological approach was of applied nature and a quasi-experimental design was employed. The study's sample consisted of 66 students divided into two groups: a control group consisting of 33 students, and an experimental group composed of 33 2nd-year secondary students from the same institution. Both groups participated in a questionnaire that had been previously validated and subjected to reliability tests. The collected and analyzed results indicate that the implementation of the mathematics laboratory as a didactic strategy has a significant effect on the mathematics learning phase for the students. This is reinforced by the evidence observed in the post-test, where the p-value was 0.000, which is less than 0.05, thus demonstrating the significance of this influence and supporting the acceptance of the determined hypothesis.